2005
DOI: 10.1016/j.jneuroim.2004.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Blood–brain barrier disruption and lesion localisation in experimental autoimmune encephalomyelitis with predominant cerebellar and brainstem involvement

Abstract: The role of the blood-brain barrier (BBB) in determining lesion distribution was assessed in an atypical model of experimental autoimmune encephalomyelitis (EAE) induced in C3H/HeJ mice by immunisation with peptide 190-209 of myelin proteolipid protein, which can result in two distinct types of EAE, each with distinct lesion distribution. Areas of the BBB showing constitutively greater permeability in naïve mice did not correlate with the lesion distribution in EAE. BBB disruption occurred only in sites of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 24 publications
(18 reference statements)
1
39
0
Order By: Relevance
“…Experiments performed in the rat using low-molecular mass molecules such as mannitol or radiolabeled ionic tracers revealed a comparable pattern of diffusion, with extravasation of ions from the lumbar spinal cord vasculature before other CNS regions (71,72). Similar observations were made in C3H/He mice, in which ascending paralysis was closely associated with HRP extravasation in the spinal cord, whereas predominant cerebellar involvement was evident only in instances of axial rotatory EAE (11). In the EAE SJL mouse model, it was proposed that the first occurrence of BBB disruption and rabbit IgG leakage occurred in the cerebellum, and then spread to the spinal cord (9).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Experiments performed in the rat using low-molecular mass molecules such as mannitol or radiolabeled ionic tracers revealed a comparable pattern of diffusion, with extravasation of ions from the lumbar spinal cord vasculature before other CNS regions (71,72). Similar observations were made in C3H/He mice, in which ascending paralysis was closely associated with HRP extravasation in the spinal cord, whereas predominant cerebellar involvement was evident only in instances of axial rotatory EAE (11). In the EAE SJL mouse model, it was proposed that the first occurrence of BBB disruption and rabbit IgG leakage occurred in the cerebellum, and then spread to the spinal cord (9).…”
Section: Discussionsupporting
confidence: 58%
“…This leads to immune cell invasion, formation of demyelinated lesions, and axonal damage (4,(6)(7)(8). Early breakdown of the BSCB in EAE has been widely documented, but the precise timing and triggers of this disruption are still a matter of debate (9)(10)(11)(12). This has prompted us to look further into the kinetics of BSCB disruption and the putative cellular candidates involved in this process.…”
mentioning
confidence: 99%
“…73,115 Considering MS-diseased BBB, it has been shown that disease severitiy could be correlated with alteration of BBB integrity, as confirmed by loss and delocalization of brain endothelilal junction proteins, like occluding., VE-cadherin and others. 67,123 Schmidt and co-workers, in two different works, 100 ; 2003b) demonstrated that long-circulating prednisolone LPs (PL) were able to localize the high tissue therapeutic levels of glucocorticalsteroid in the inflamed cerebral area of autoimmune EAE rats model 39 as compared with an equivalent dose given as free drug with a following reduction of inflammation and a significantly improvement in the disease course of (AT)-EAE.…”
Section: Huntington' S Diseasementioning
confidence: 99%
“…The development and progression of clinical signs in EAE are associated with loss of blood-brain barrier (BBB) integrity and upregulation of adhesion molecules expression in CNS tissues, resulting in the migration of vascular inflammatory cells into the CNS compartment [2,3]. This inflammatory cascade triggers upregulation of various proinflammatory mediators produced by infiltrating leukocytes and resident glial cells in the CNS, which are determining factors in the tissue damage [4,5].…”
Section: Introductionmentioning
confidence: 99%